Light Pyrotechnics Using Gunpowder Derived from Fly Ash Bottom Ash (FABA) Waste and Activated Carbon - Siregar, Fuad Idris; Prasojo, Agus Eko; Julianingrum, Shavira Triana; Aulia, Desi Rahma Yanti; Wardha, Sophia Nafisa; Gita, Mutiara (Indonesian Journal of Chemical Studies, 2024)
Pyrotechnic materials are a category of materials that are often used in various applications, including military activities, lighting, signaling, and combat effects. In this study, an experiment was conducted to create a light pyrotechnic material using gunpowder, which is a mixture of potassium nitrate, sulfur, and activated carbon. The manufacturing process involved the activation of carbon from fly ash bottom ash (FABA) waste and the composition of different pyrotechnic materials. The experiment involved testing pyrotechnic compositions with varying ratios of KNO3 : carbon : sulfur. The results showed that the composition with a ratio of 15 : 7.5 : 7.5 produced the highest light intensity, reaching 104 lux, and provided optimal visual effects. In addition, the relative proportions of oxidizer, carbon and sulfur affected the type of pyrotechnic effect produced. Pyrotechnic light generation from gunpowder could be considered successful, and the best composition for spectacular visual effects was a ratio of 15 : 7.5 : 7.5. However, sufficient caution and knowledge were required in the use of pyrotechnic materials to ensure safety and compliance with applicable regulations.